Feasibility study of submerged floating tunnels with vertical and inclined combined tethers. (1st December 2022) - Jeong, Kiwon; Min, Seongi; Jang, Minseo; Won, Deokhee; Kim, Seungjun
Abstract: An appropriate mooring system and tunnel body are required to ensure the dynamic stability and serviceability of submerged floating tunnels (SFTs) under various environmental loads. This paper presents a feasibility study of SFTs with vertical and inclined combined tethers. The basic concept of this system is to provide the vertical and horizontal stiffness of the tunnel using the vertical and inclined combined tethers. To evaluate this type of SFT, a hydrodynamic analysis was performed in the time domain using the finite element program ABAQUS-AQUA. The spacing of the tethers and inclination angle of the inclined tethers were considered as the parameters. An irregular wave with a 100-year return period was considered as the environmental load. Through the numerical analysis, the time series for the tether stress, tunnel displacement, and internal forces were obtained. Based on the obtained structural response, the adequacy of the strength and fatigue design of the vertical and inclined tethers combined mooring system was investigated. Through an analytical study, it was found that this mooring type could be effectively applied, owing to its structural efficiency. According to the numerical analysis, the combined mooring system satisfies the design conditions when the tether spacing is less than 40.0 m and inclination angle is 45.0°. Highlights: To properly control the motion, a mooring type using inclined and vertical tethers was proposed. The feasibility of this mooring system was analyzed using a hydrodynamic-based global system analysis. For the proposed model, a 100-year return-period wave load was applied using the tether spacing and inclination angle. The design adequacy was judged based on DNV and API design recommendations.